The Analysis of Mobile WiMAX and LTE using MIMO technique - Garg, Roopali; Singla, Shafi (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
A quality of service is a fundamental component of the 4G broadband network for satisfactory service delivery by evolving internet application to end user, and managing the network resources. The 4G technology has emerged one of the most fruitful technologies as it supports large number of applications including VOIP, video conferencing, file transfer, video streaming and web browsing. IEEE 802.16E, IEEE 802.16M and LTE along with various application and QoS requirement also support Multiple-Input-multiple-output (MIMO) techniques including Spatial Multiplexing (SM), Space Time Block Coding(STBC) and Eigen Beam-forming (BM).In the paper we will study Physical, MAC layer of WiMAX and LTE. We will also study MIMO techniques. In this paper Â the detailed study of the throughput for a MIMO mobile WiMAX system and LTEÂ  under two different PHY PER QoS threshold. Various modulation and channel coding techniques have been applied.